Barriers and Facilitators of Family Planning Use in Fishing Communities of Lake Victoria in Uganda. (July 2020) - Nanvubya, Annet; Wanyenze, Rhoda Kitty; Kamacooko, Onesmus; Nakaweesa, Teddy; Mpendo, Juliet; Kawoozo, Barbarah; Matovu, Francis; Nabukalu, Sarah; Omoding, Geoffrey; Kaweesi, Jed; Ndugga, John; Bagaya, Bernard; et al.
Introduction: Family planning (FP) is a key element in the conduct of research and is essential in managing family sizes. Although fishing communities (FCs) are targeted populations for HIV prevention research, their FP practices are poorly understood. We explored barriers and facilitators of FP use in FCs of Lake Victoria in Uganda.Methods: We employed a mixed-methods approach comprising a cross-sectional survey, in-depth interviews, and focus group discussions in 2 FCs. Multivariable logistic regression was used to analyze quantitative data and a thematic approach to generate themes from the qualitative data.Results: Up to 1410 individuals participated in the survey and 47 in the qualitative study. Just over a third (35.6%) used FP. The most commonly used methods were condoms, pills, and injectables. In Kigungu community, participants whose religion was Anglican and Muslim were more likely to use FP than Catholics (adjusted odds ratio [aOR] 1.45; 95% CI 1.05-1.99 and aOR 1.45; 95% CI 1.05-2.07, respectively). Participants were more likely to use FP if they had satisfactory FP knowledge compared to those with no satisfactory FP knowledge (aOR 1.79; 95% CI 1.23-2.61), or if they were married compared to their single counterparts (aOR 1.84; 95% CI 1.32-2.57). In both communities, participants were more likely to use FP if they had 2 or more sexual partners in the past 12 months than those with less than 2 sexual partners (aOR 1.41 95% CI 1.07-1.87 and aOR 2.60; 95% CI 1.36-4.97). Excessive bleeding and delayed fecundity; fertility desire; gender preferences of children; method stock outs and lack of FP trained personnel constituted barriers to FP use. There were also cultural influences in favor of large families.Conclusion: FP use in FCs is suboptimal. Barriers of FP use were mainly biomedical, religious, social, and cultural, which underscores a need for FP education and strengthening of FP service provision in FCs.